Latihan Kerja dan Kegiatan Produksi Narapidana Sebagai Model Pembinaan Kemandirian dan Pencapaian Lembaga Pemasyarakatan Industri - Muh Khamdan Khamdan; Wiharyani; Rini Setiawati (Politeknik Negeri Cilacap, 2024)
Following a rigorous, carefully concerns and considered review of the article published in Madani : Indonesian Journal of Civil Society to article entitled “Latihan Kerja dan Kegiatan Produksi Narapidana Sebagai Model Pembinaan Kemandirian dan Pencapaian Lembaga Pemasyarakatan Industri” Vol 6, No 2, pp. 43-53, August 2024, DOI: https://doi.org/10.35970/madani.v6i2.2219. This paper has been found to be in violation of the Madani : Indonesian Journal of Civil Society Publication principles and has been retracted. The article contained redundant material, the editor investigated and found that the paper published in JMM (Jurnal Masyarakat Mandiri), Vol. 8, No. 2 (August 2024), pp. 1957-1967, DOI: https://doi.org/10.31764/jmm.v8i2.21782, entitled